Ethical investment and workplace bullying: consonances and dissonances. (1st January 2003) - McCarthy, P.; Sheehan, M.; Barker, M.; Henderson, M.
The discourses of corporate social responsibility and workplace bullying have both given expression to concerns about degrading impacts of corporations on the natural and social environments by corporations bent on meeting global market pressures. "Bullying at work" has emerged as a widely acknowledged descriptor of a diversity of unreasonable and inappropriate behaviours in these circumstances. Corporate social responsibility and ethical investment are also being promulgated internationally as an accommodation to perceived negative impacts of corporations on social and natural ecologies. Despite evidence of the impacts of bullying, businesses have generally been reluctant to address the issue, due at least in part to a lack of awareness of the costs and of benefits to be gained by taking action. Ethical investment rating criteria, however, appear to ignore the dimension of responsible treatment of employees in favour of environmental and broader external stakeholder concerns. This paper reports findings of a study of the relations of corporate social responsibility and bullying.